Peran Label Halal, Brand Ambassador dan Gaya Hidup Terhadap Keputusan Pembelian Skincare Merek Wardah di Kota Semarang - Ardelia Nisa Adiana; Mahmud; Dian Nuswantoro (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to analyze the influence of the halal label, brand ambassador and lifestyle on purchasing decisions for wardah brand skincare products in Semarang City. This research involved 96 respondents using wardah products from an unlimited population using a purposive sampling technique. Purchasing decisions are the independent variables consist of halal label, brand ambassador and lifestyle. Data analysis was carried out using multiple linear regression. The research results show that there is a positive influence of the three independent variables on purchasing decisions for wardah skincare products.